Guillain Barré syndrome and SARS-CoV-2 infection: Report of two cases in Peru. - Segura-Chávez, Darwin (2021)
Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus, shows mainly clinical manifestations at the respiratory level. It can affect, however, other organs and systems, including the central nervous system, generating neurological manifestations that include the Guillain Barré Syndrome (GBS). We present the cases of two male patients, aged 35 and 46, with GBS, one classified as AMAN and the other as AIDP. Both patients showed positive serology for SARS-CoV-2 and reported respiratory symptoms prior to the weakness condition. RT-PCR in pharyngeal secretion and CSF was negative in both cases. The infection by SARS-CoV-2 was confirmed by the total antibody test in serum through a positive CLIA immunoassay, positive for IgG in the two cases. The characteristics of the cases support a possible postinfectious relationship between SARS-CoV-2 and GBS, and open as well the possibility that despite being asymptomatic or having mild respiratory symptoms, some patients may develop post- infectious complications such as GBS.